Analysis of genetic variability in Turner syndrome linked to long-term clinical features - Suntharalingham, Jenifer P.; Ishida, Miho; Cameron-Pimblett, Antoinette; McGlacken-Byrne, Sinead M.; Buonocore, Federica; del Valle, Ignacio; Madhan, Gaganjit Kaur; Brooks, Tony; Conway, Gerard S.; Achermann, John C. (Frontiers in Endocrinology, 2023)
Background: Women with Turner syndrome (TS) (45,X and related karyotypes) have an increased prevalence of conditions such as diabetes mellitus, obesity, hypothyroidism, autoimmunity, hypertension, and congenital cardiovascular anomalies (CCA). Whilst the risk of developing these co-morbidities may be partly related to haploinsufficiency of key genes on the X chromosome, other mechanisms may be involved. Improving our understanding of underlying processes is important to develop personalized approaches to management. Objective: We investigated whether: 1) global genetic variability differs in women with TS, which might contribute to co-morbidities; 2) common variants in X genes - on the background of haploinsufficiency - are associated with phenotype (a “two-hit” hypothesis); 3) the previously reported association of autosomal TIMP3 variants with CCA can be replicated. Methods: Whole exome sequencing was undertaken in leukocyte DNA from 134 adult women with TS and compared to 46,XX controls (n=23), 46,XX women with primary ovarian insufficiency (n=101), and 46,XY controls (n=11). 1) Variability in autosomal and X chromosome genes was analyzed for all individuals; 2) the relation between common X chromosome variants and the long-term phenotypes listed above was investigated in a subgroup of women with monosomy X; 3) TIMP3 variance was investigated in relation to CCA. Results: Standard filtering identified 6,457,085 autosomal variants and 126,335 X chromosome variants for the entire cohort, whereas a somatic variant pipeline identified 16,223 autosomal and 477 X chromosome changes. 1) Overall exome variability of autosomal genes was similar in women with TS and control/comparison groups, whereas X chromosome variants were proportionate to the complement of X chromosome material; 2) when adjusted for multiple comparisons, no X chromosome gene/variants were strongly enriched in monosomy X women with key phenotypes compared to monosomy X women without these conditions, although several variants of interest emerged; 3) an association between TIMP3 22:32857305:C-T and CCA was found (CCA 13.6%; non-CCA 3.4%, p<0.02). Conclusions: Women with TS do not have an excess of genetic variability in exome analysis. No obvious X-chromosome variants driving phenotype were found, but several possible genes/variants of interest emerged. A reported association between autosomal TIMP3 variance and congenital cardiac anomalies was replicated.